The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1109/tns.2005.862983
|View full text |Cite
|
Sign up to set email alerts
|

Model-based registration of X-ray mammograms and MR images of the female breast

Abstract: We present a new approach for automatic registration of X-ray mammograms and MR images. Multimodal breast cancer diagnosis is supported by automatic localization of small lesions, which are only visible in the mammograms or in the MR image. To cope with the huge deformation of the breast during mammography, a finite element model of the deformable behavior of the breast is applied during the registration. An evaluation of the registration with six clinical data sets resulted in an accurate localization with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
76
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 10 publications
(11 reference statements)
1
76
0
Order By: Relevance
“…The registration method is based on a method originally developed for the registration of Magnetic Resonance Tomography images with X-ray mammograms [9,22] and was successfully applied for the registration of USCT images with X-ray mammograms. The obtained accuracy for an automated registration (TRE 11.9 mm) is slightly better than for the registration with MRI images (13.2 mm), well within the range other MRI-to-mammography registration approaches in literature [20,51] and as well in a range which might assist radiologists in multimodal diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The registration method is based on a method originally developed for the registration of Magnetic Resonance Tomography images with X-ray mammograms [9,22] and was successfully applied for the registration of USCT images with X-ray mammograms. The obtained accuracy for an automated registration (TRE 11.9 mm) is slightly better than for the registration with MRI images (13.2 mm), well within the range other MRI-to-mammography registration approaches in literature [20,51] and as well in a range which might assist radiologists in multimodal diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…[22,39]. At first the USCT volume is rigidly aligned with the X-ray mammogram in anteroposterior direction at the chest wall.…”
Section: Image Registrationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, an 8% error in c 1 results in 2 mm RMS errors in prediction accuracy. However, this analysis suggests that larger errors in the estimation of c 1 will still satisfy the sub-5 mm accuracy required for clinical applications (Ruiter et al 2004). …”
Section: Validation Of the Optimized Materials Parametermentioning
confidence: 98%
“…This paper focuses on the construction of a modeling framework that can reasonably accurately predict the compressive deformations, in order to match the deformed model to the mammogram images (step 3). It has been reported that model predictions should be better than 5 mm accurate compared to actual deformation to be useful for early breast cancer diagnosis (Ruiter et al 2004). In constructing the modeling framework, we use a systematic approach to validate each aspect of our model using carefully controlled experimental studies.…”
Section: Biomechanical Model: the Motivationmentioning
confidence: 99%